Pengaruh Ukuran dan Kedalaman Geotekstil Teranyam Tipe HRX 200 terhadap Daya Dukung Ultimit dan Penurunan Tanah Lempung Lunak - Anita Widianti , Azmania , Budi Kurniawan Thirayo (Semesta Teknika, 2013)
Geotextile as one of improvement material in soft clay soil has been widely used.  This study aims to examine the effect of geotextile dimention and placement depth on ultimate bearing capacity, settlement and Bearing Capacity Ratio of soft clay soil. This test was conducted on a series of square plate foundation loading of 10 cm width on clay soil sample and installing one layer of geotextile-improvement inside with several dimention variations and geotextile depth. Clay soil is on soft condition taken into a box model made of steel plate with the dimention of 120 cm x 120 cm x 100 cm. The result of this research shows that dimension and depth of geotextile affected the bearing capacity and settlement of soft clay soil. There were improvement in ultimate bearing capacity of as high as 3 times higher for geotextile 3Bx3B; 4 times higher for geotextile 4Bx4B; 5 times higher for geotextile 5Bx5B and 6 times higher for geotextile 6Bx6B comparing with bearing capacity of non supported-clay soil. Decreasing of settlement on clay soil was observed on the 3Bx3B improvement (twice lower), and 3 times lower, 4 times lower and 5 times lower for 4Bx4B, 5Bx5B, 6Bx6B, respectively. Geotextile which placed at a depth of 0.4 B and 0.8 B resulted in increased ultimate bearing capacity by 3.13 times. Dimension and depth geoxtile also affect the value of BCR. The highest BCR was on the dimention 6Bx6B on the depth of 0.6 B.